2010
DOI: 10.1530/rep-09-0518
|View full text |Cite
|
Sign up to set email alerts
|

The role of RXFP2 in mediating androgen-induced inguinoscrotal testis descent in LH receptor knockout mice

Abstract: LH receptor knockout (LhrKO) male mice exhibit a bilateral cryptorchidism resulting from a developmental defect in the gubernaculum during the inguinoscrotal phase of testis descent, which is corrected by testosterone replacement therapy (TRT). In vivo and in vitro experiments were conducted to investigate the roles of the androgen receptor (AR) and RXFP2 signals in regulation of gubernacular development in LhrKO animals. This study demonstrated that AR and RXFP2 proteins were expressed in the gubernaculum dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 49 publications
1
47
0
1
Order By: Relevance
“…Abiraterone, a potent inhibitor of CYP17A1 enzyme (36), abolished A4 secretion and reduced expression of INSL3 and RXFP2 mRNA by ∼50%, supporting the notion of a mutual, positive autoregulatory loop linking thecal INSL3-RXFP2 signaling and androgen synthesis. Our evidence that ovarian (thecal) expression of RXFP2 is positively regulated by androgens concurs with the recent observation in male mice that testosterone administration to androgen-deficient LHCGR-null mutants upregulated RXFP2 expression in the gubernaculum (37).…”
Section: Discussionsupporting
confidence: 92%
“…Abiraterone, a potent inhibitor of CYP17A1 enzyme (36), abolished A4 secretion and reduced expression of INSL3 and RXFP2 mRNA by ∼50%, supporting the notion of a mutual, positive autoregulatory loop linking thecal INSL3-RXFP2 signaling and androgen synthesis. Our evidence that ovarian (thecal) expression of RXFP2 is positively regulated by androgens concurs with the recent observation in male mice that testosterone administration to androgen-deficient LHCGR-null mutants upregulated RXFP2 expression in the gubernaculum (37).…”
Section: Discussionsupporting
confidence: 92%
“…Where convincing signals are detected, it can be difficult to clearly identify the target of selection within a region, and even more difficult to establish the link between selection and its morphological consequence. In this study the strongest selection signal was identified immediately adjacent to RXFP2 , a gene involved in reduced bone mass and sexual maturation [47],[48]. Strong evidence supports that RXFP2 was targeted by breeding for the removal of horns, likely to be one of the oldest morphological modifications that accompanied domestication [49],[50].…”
Section: Discussionmentioning
confidence: 79%
“…A genome-wide association study was conducted using 36,000 SNPs and determined the main genetic candidate for horns to be RXFP2 , an autosomal gene with known involvement in determining primary sexual characteristics in humans and mice [37-39]. Evidence from additional SNPs in and around RXFP2 supports a new model of horn-type inheritance in Soay sheep, and for the first time sheep with the same horn phenotype but different underlying genotypes can be identified.…”
Section: Progress Of Gwas In Domestic Animalsmentioning
confidence: 99%